Marketing transformation : marketing practice in an ever changing world : proceedings of the 2017 Academy of Marketing Science (AMS) World Marketing Congress (WMC) /: marketing practice in an ever changing world : proceedings of the 2017 Academy of Marketing Science (AMS) World Marketing Congress (WMC). ([2018]) - Unknown
No abstract available